Lifetime Felony Disenfranchisement in Florida, Texas, and Iowa: Symbolic and Instrumental Law - Sennott, Christie (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The writers discuss lifetime felony disenfranchisement (LFD) laws, which are well known to have much of their origins in American racism and the Civil War. They demonstrate how the instrumental use of LFD law has continued unabated in Florida and how the distinction between instrumental law and symbolic law—the former intended to control behavior and the latter more concerned with using law to make a public statement—can be used to explain the repeal of LFD legislation in Texas and its retention in Iowa. They show how state institutions organize and enforce racial politics through policies that were once explicitly and are now implicitly racial.